Assessing the Effectiveness of Artistic Place-Based Climate Change Interpretation. Issue 2 (November 2014) - Barrett, Austin; Mowen, Andrew J.
This paper analyzed the effectiveness of an artistic place-based climate change interpretive program at Glacier National Park in Montana. Utilizing the framework of place-based climate change communication and the use of artistic interpretive methods, this study offered support for the efficacy of communicating climate change at a climate-impacted location. The survey instrument assessed emotional, intellectual, and stewardship response measures, as well as climate change response outcomes. Regardless of the artistic program format (live music or poetry), visitors responded favorably to all three of the interpretive outcome domain measures. Statistical comparisons found a number of differences between interpretive outcome measures in regard to motivation and visitor characteristics. By utilizing artistic approaches, this study offers support for the growing body of research about the power of place-based interpretive messaging to engage the public on the issue of climate change.